Significance of Prisons in the light of Islamic Teachings: جیل خانہ جات کی ضرورت و اہمیت اسلامی تعلیمات کی روشنی میں - Ullah, Amman; Ahmad, Prof: Dr. Matloob (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
Jail means the place in which the accused persons are kept for investigation or criminals are kept for punishment. In jail, prisoners lose their right of freedom. The aim to establish jail is to frighten the unseemliness people, betterment of unconscious and ignorant persons and to give punishment to the criminals, so that peace of society may be maintained. The regular system of jail was not present in the period of Holy Prophet (ﷺ) and caliph Hazrat Abu Bakar (R.A), but the concept of imprisonment existed. Hazrat Umer (R.A) Bought the house from Safwan bin Umayyah and used it as a jail in his reign. That was also present in the reign of Hazrat Usman (R.A). When Hazrat Ali (R.A) Became caliph, he constructed first regular jail which was given the name “Nafay”. The Second jail was “Mukhaius”. In Short, the concept of jail is taken from the Holy Quran, Hadith, remains of Sahaba and consensus of the Ummah.